ROS-augmented and tumor-microenvironment responsive biodegradable nanoplatform for enhancing chemo-sonodynamic therapy. (March 2020) - An, Jie; Hu, Yong-Guo; Cheng, Kai; Li, Cheng; Hou, Xiao-Lin; Wang, Gang-Lin; Zhang, Xiao-Shuai; Liu, Bo; Zhao, Yuan-Di; Zhang, Ming-Zhen
Abstract: Nanocarrier for augmenting the efficacy of reactive oxygen species (ROS) by tumor microenvironment (TME) has become an emerging strategy for cancer treatment. Herein, a smart biodegradable drug delivery nanoplatform with mitochondrial-targeted ability, pH-responsive drug release and enzyme-like catalytic function is designed. This efficient ROS-generating platform uses ultrasound with deeper penetration capability as excitation source for combined chemotherapy and sonodynamic therapy (SDT) of tumor. In vitro experiments show that the nanoplatform can co-load Ce6 and DOX and be degraded in slight acid environment, and the DOX release rate is 63.91 ± 1.67%. In vivo experiments show that the nanoplatform has extremely biosafety and can be enriched in tumor site and excluded from body after 24 h. More significantly, after combined treatment, the tumors are eliminated and the mice still survive healthily without recurrence after 60 d. This is because not only it can achieve mitochondrial targeting and use platinum particle to increase oxygen content in TME to enhance the effect of SDT, but also it can use weak acidic TME to accelerate drug release to achieve the combination of chemotherapy and SDT. The probe provides a new strategy for designing ROS-based nanoplatform for the treatment of malignant tumor.